PSYCHOLOGICAL FEATURES OF THE FORMATION OF NONVERBAL COMMUNICATION OF PUPILS STUDYING IN THE EDUCATIONAL ART DIRECTION (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article explores the psychological aspects of the formation of nonverbal communication skills in pupils studying in the direction of Fine Arts. In educational settings, pupils are taught how to improve nonverbal communication skills through feedback processes and training.